Reatividade de fontes de silício no solo e sua acumulação nas plantas de arroz e de sorgo - Ferreira, Barbara Campos (2017)
Silicon (Si) is a beneficial element for plants, especially grasses, such as rice and sorghum, which can absorb it in greater amounts. The main Si sources are natural (rocks) or byproducts of steel and phosphate fertilizer industries. There are several Si sources in the market; however, it is important to identify those with greater potential of supplying Si to soil and plants. This study determined the reactivity of five sources in the soil and supplying silicon to the rice and sorghum. Thus, two experiments were done, one incubation test and one experiment in the greenhouse (biological test). Both experiments were done with two soil types: Neossolo Quartzarênico órtico (RQo), with 15% sand and 2.2 mg dm-3 Si (CaCh 0.01 mol L-1) and Latossolo Vermelho distrófico (LVd) with 84% sand and 4.8 mg dm-3 Si (CaCh 0.01 mol L-1). Silicon sources were: Dunito, Nickel slag (Ni), Thermophosphate MA (Morro Azul), TMF II and Agromil, at 200 and 400 kg ha-1 Si, and the standard source Wollastonite at equivalent doses of 100, 200, 400 and 600 kg ha-1 Si for the incubation test, and the doses 100, 200, 400 and 600 kg ha-1 Si in the biological test for all sources. The experimental design of the incubation test was completely randomized, as a 6x2+1 (six Si sources, two Si doses and control with no Si application) factorial, with four replications. The following variables were analyzed after 60 days of incubation: soil available Si (CaCh 0.01 mol L-1), Ca, Mg, pH and the equivalent in calcium silicate - Wollastonite (Eq. SiCa). The biological test was done in randomized blocks, as a 6x4+1 factorial, with four replications and two consecutive crops (rice and sorghum). Each experimental unit consisted of a 5-kg pot containing 10 rice plants of cultivar IRGA 424, and for the second crop, 5 sorghum plants of cultivar 1G 100 from Dow Agrosciences. The variables analyzed were: soil Si, shoot dry matter, plant Si contents and Si accumulated in the shoots. The amount of product applied in both tests was determined based on total Si total contents (g kg-1) of each source: Thermophosphate MA: 133, Dunito: 180, Ni slag: 298, TMF II: 41, Agromil: 342 and Wollastonite: 244. The sources TMF II, Wollastonite and Thermophosphate MA were the most effective in supplying Ca to the soil and in increasing pH. Dunito and Thermophosphate MA were the most effective in supplying Mg. The most effective sources for supplying Si to the soil and to plants were Thermophosphate MA and the standard Wollastonite, reflecting positively on Si accumulated by both crops. The greater the Si dose, the greater was the availability of the element for both soil and for both crops, rice and sorghum, when applyed via Wollastonite and Thermophosphate. There was no positive effect of silicon sources on crop dry matter, except for Wollastonite.